2023
DOI: 10.1002/ldr.4550
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in fine root dynamics in relation to tree girth size in sub‐tropical sal (Shorea robusta) forests

Abstract: In forest ecosystems, the rapid turnover of fine roots (≤2 mm in diameter) is a major pathway of carbon and nutrient flow from plants to the soil. This study was conducted to determine how fine root biomass (FRB), productivity (FRP) and turnover (FRT) are affected by site characteristics, seasonal variation, soil depth and tree girth size in sub‐tropical sal forest ecosystem. Four sites (S1, S2, S3 and S4) were established in the Bhabhar region of Nainital istrict, Uttarakhand, India within an elevational rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 64 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…In the Central Himalayan region, studies were also focused on the impact of forests on soil health and carbon but also developed methods for large‐scale quantification of soil organic carbon. Given the role of fine root biomass (FRB), productivity (FRP), and turnover (FRT) as a pathway of carbon and nutrients from plants to the soil, Pandey et al (2023) examined the rapid turnover of fine roots (≤2 mm in diameter) in a sub‐tropical sal ( Shorea robusta ) forest ecosystem in Nainital district in Uttarakhand. They found that FRB was highest for the uppermost, organo‐mineral‐rich soil depth (0–20 cm) at 1 m distance from the tree bole and decreased with increasing soil depth, increasing girth size of tree bole and distance from the tree bole while fine root runover (FRT) showed the opposite pattern.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In the Central Himalayan region, studies were also focused on the impact of forests on soil health and carbon but also developed methods for large‐scale quantification of soil organic carbon. Given the role of fine root biomass (FRB), productivity (FRP), and turnover (FRT) as a pathway of carbon and nutrients from plants to the soil, Pandey et al (2023) examined the rapid turnover of fine roots (≤2 mm in diameter) in a sub‐tropical sal ( Shorea robusta ) forest ecosystem in Nainital district in Uttarakhand. They found that FRB was highest for the uppermost, organo‐mineral‐rich soil depth (0–20 cm) at 1 m distance from the tree bole and decreased with increasing soil depth, increasing girth size of tree bole and distance from the tree bole while fine root runover (FRT) showed the opposite pattern.…”
Section: Review Of Papers Published In This Issuementioning
confidence: 99%
“…The studies in this special issue found that agroforestry improves soil outcomes while also providing socio‐economic benefits by supplementing income of farmers (Karki et al, 2022; Nienkerke & Patt, 2022). The articles on forests quantify various soil‐based ecosystem services (Kumar, Roy, et al, 2022; Pandey et al, 2023) and report that forest degradation reduces these services (Shukla et al, 2022; Thakrey et al, 2022). In the case of soil salinization, also, studies tested different methods to reduce salinization in different local conditions (Jha et al, 2022; Meena et al, 2022; Neha et al, 2022).…”
Section: Synthesis and Conclusionmentioning
confidence: 99%
“…Fine root production is a fundamental component of forest productivity because it contributes to 22% -40% of terrestrial net primary production (Lima et al 2010;Finér et al 2011a;Luke McCormack et al 2013;Pandey et al 2023). Fine root production and turnover is one of the important pathways of carbon and nutrient cycling in forest ecosystems (Nadelhoffer and Raich 1992;Matamala et al 2003;Jourdan et al 2008;Germon et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wetland ecosystem and its vegetation provide a wide range of ecosystem goods and services to the inhabitants ( Gosain et al., 2015 ; Fartyal et al., 2022 ). Overexploitation of natural resources has created a big gap between the demand and supply of the natural goods ( Manral et al., 2020 ; Pandey et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%